MAPPING ENTREPRENEURIAL LEADERSHIP OF SCHOOL PRINCIPALS RESEARCH: A BIBLIOMETRIC ANALYSIS - Alberthin Gabriela Reskir; Tanwey G. Ratumanan; Paul Arjanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study maps the development of research on entrepreneurial leadership of school principals using bibliometric analysis. Bibliographic data were retrieved from the Scopus database and screened using the PRISMA 2020 flow procedure. From 397 initial records, 59 English-language articles and reviews were selected for analysis. The dataset covered publications from 2014 to 2026, 45 sources, 150 authors, and 7,127 references. The analysis examined annual scientific production, source productivity, country scientific production, international collaboration, author keywords, keyword co-occurrence, thematic mapping, and trend topics. The findings show that the field has grown unevenly but steadily, with publication peaks in 2018, 2020, and 2024. Frontiers in Education and the International Journal of Educational Management were among the most productive sources. Indonesia, Australia, Malaysia, South Africa, Cyprus, Hong Kong, Finland, the United States, and the United Kingdom occupied visible positions in country productivity, while international collaboration remained relatively limited. The keyword and thematic analyses show that school principals, entrepreneurial leadership, school leaders, school leadership, entrepreneurship education, innovation, entrepreneurial competence, and educational management form the core conceptual structure of the field. The study contributes by clarifying the publication, geographical, and thematic structure of entrepreneurial school leadership research and identifying future directions for educational management studies.